A study on the efficiency of current methods of breeding and testing for wheat improvement in the Western Cape Province - Pakendorf, Klaus Werner (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD (Agric)) -- University of Stellenbosch, 1977.